2021
DOI: 10.3390/ijerph18136937
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Discharge from Hospital after Myocardial Infarction: A Cross-Sectional Study

Abstract: Myocardial infarction (MI) is a common cause of cardiovascular deaths. Education of patients with myocardial infarctions essential to prevent further cardiovascular events and reduce the risk of mortality. The study aimed to evaluate the associations between patients’ readiness for hospital discharge after myocardial infarction, acceptance of illness, social, demographic, and clinical factors. The study used a cross-sectional design and included 102 patients, who were hospitalized for myocardial infarction aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…This review found that nurse-led interventions increased the self-care capacity of patients who participated in educational programs, as corroborated by other studies [ 49 , 50 ]. After hospital discharge, these patients usually showed psychological disorders, changes in family dynamics, and even professional problems; therefore, home monitoring and social support allow them to improve self-efficacy [ 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…This review found that nurse-led interventions increased the self-care capacity of patients who participated in educational programs, as corroborated by other studies [ 49 , 50 ]. After hospital discharge, these patients usually showed psychological disorders, changes in family dynamics, and even professional problems; therefore, home monitoring and social support allow them to improve self-efficacy [ 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…Patients who were older, unrelated, lived alone, less educated, and unemployed were less prepared for discharge. And the acceptance of illness was positively associated with RHD (Hydzik et al, 2021). The effective implementation of discharge planning for MI patients should include an assessment of factors influencing RHD and acceptance of illness.…”
Section: Resultsmentioning
confidence: 97%
“…Physical evaluation in MI patients includes cardiac symptoms, electrocardiogram (ECG) changes, cardiac enzymes, angiography, echo, exercise test, examination of catheterization, angiography, angioplasty, etc. (Hydzik et al, 2021;Kosobucka et al, 2020).…”
Section: Defining Attributesmentioning
confidence: 99%
“…Preparing the patient for autonomy after MI allows them to return to normal life and increases disease acceptance. Therefore, a patient's RHD is recognized as an important component in clinical practice (Hydzik et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%